2021
DOI: 10.1111/1759-7714.13898
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal undifferentiated pleomorphic sarcoma with pleural effusion cytopathologically misdiagnosed as epithelial malignant pleural mesothelioma: An autopsy case report

Abstract: Undifferentiated pleomorphic sarcoma (UPS) is a new disease in the World Health Organization's classification of tumors of soft tissue and bone published in 2013. Primary mediastinal UPS is rare, especially with pleural effusion. Herein, we describe the pathological findings of pleural effusion followed by mediastinal UPS, which was initially misdiagnosed as epithelial malignant pleural mesothelioma (MPM). The cytopathological findings of the pleural effusion cell block often contribute to the diagnosis of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The specific etiology of PUS is unknown and may be related to genetic aberrations and radiotherapy ( 10 ). To the best of our knowledge, only six cases of PUS were previously reported in the mediastinum ( 4 – 9 ) and the present one is the first report on PUSM. The present study aimed to report and analyzed this case along with the relevant literature review.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The specific etiology of PUS is unknown and may be related to genetic aberrations and radiotherapy ( 10 ). To the best of our knowledge, only six cases of PUS were previously reported in the mediastinum ( 4 – 9 ) and the present one is the first report on PUSM. The present study aimed to report and analyzed this case along with the relevant literature review.…”
Section: Discussionmentioning
confidence: 54%
“…The mass was large, and the maximum diameter was 19 cm ( 4 ). An autopsy revealed that the tumor recurred into the pericardium, heart or great vessels ( 7 9 ). A physical examination of the present patient revealed that the mass was located in the anterior mediastinum with a clear boundary and irregular nodules with a maximum diameter of 5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because UPS lacks special clinical manifestations in the early stage and features no specific changes on auxliary examinations, histopathological examination has become the gold standard for its diagnosis, presenting microscopically as a high-grade sarcoma without any specific differentiation direction. According to the majority of publications, UPS lacks specific immunohistochemical markers, which is an excluded diagnosis ( 14 ). Vimentin, WT-1, CD99, and EMA can be expressed in UPS ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the majority of publications, UPS lacks specific immunohistochemical markers, which is an excluded diagnosis ( 14 ). Vimentin, WT-1, CD99, and EMA can be expressed in UPS ( 14 , 15 ). However, Masamichi ( 16 ) et al.…”
Section: Discussionmentioning
confidence: 99%